Team Assisted Individualization (TAI) Conveyed through Adobe Flash CS3 to Increase Participation and English Vocabulary Mastery for the Second Semester Students at Akademi Bahasa Balikpapan - Muhammad Rochman (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
Most lecturers were still rely on the lecturing method to deliver material, how they use the media (whiteboard, pictures, cards) and their teaching methods are less than optimal and catch students’ attention, which degrade the quality of the learning process. The result of preliminary study shows that the previous English summative test score were still 50. It means that their score average was still for all the students in that Second Semester. Therefore, it is necessary to pay attention to instruction that can foster vocabulary development. The research design of this study was classroom action research, which focuses on a particular group of students in a certain classroom. The setting of the research was Akademi Bahasa Balikpapan. The subjects of the research were the second-semester students who took English vocabulary lesson. Data collection techniques adapted to the data to be obtained to determine students' achievement of English test by using Adobe Flash CS3 Media in vocabulary building project assessment in making animation collection that were contained with English sentences and their meanings. To determine the role of the student in the learning process with the assessment of the affective aspects of the observations obtained during the teaching and learning activities take place and the role of the student participation. The results showed that it could be concluded that the implementation of the Adobe Flash TAI strategy in teaching vocabulary could enhance the students’ Project on groups’ laptop in vocabulary the text. The observation checklist and field note proved the students’ involvement in text given.